The Effect of Lower Limb Revascularization on Flow, Perfusion, and Systemic Endothelial Function: A Systematic Review. (March 2021) - Normahani, Pasha; Khosravi, Sodabeh; Sounderajah, Viknesh; Aslam, Mohamed; Standfield, Nigel J.; Jaffer, Usman
Peripheral arterial disease (PAD) is associated with reduced lower limb blood flow and tissue perfusion. The consequent reduction in vessel wall shear stress as well as ischemia–reperfusion injury has also been associated with systemic endothelial dysfunction and inflammation. We aimed to explore the impact of lower limb revascularization on (1) lower limb blood flow, (2) tissue perfusion, and (3) systemic endothelial function. We performed a systematic literature search using the MEDLINE, Embase, and Web of Science databases. Eligible studies measured changes in lower limb blood flow, perfusion, or systemic endothelial function following revascularization for the treatment of symptomatic PAD. We found 19 eligible studies, which were limited by considerable heterogeneity. Current evidence suggests that revascularization has a positive effect on flow, perfusion, and systemic endothelial dysfunction. Any changes may take a number of weeks to become apparent. There is a need for well-designed studies to explore the association between flow, perfusion, and endothelial dysfunction.